Respuesta :
The box attains a velocity of 27 m/s in 3 seconds from rest. That means the velocity become 27m/s from 0m/s. Then, the acceleration would be:
acceleration= final velocity - initial velocity / time
acceleration= (27m/s- 0m/s) / 3second= 9m/s2
The final velocity if the time is 6 second would be:
acceleration= final velocity - initial velocity / time
9m/s2= (final velocity - 0m/s) / 6s
final velocity= 9m/s2 * 6s= 54m/s
The distance would be:
distance= (final velocity + initial velocity) * time / 2
distance= (54m/s+ 0m/s) * 6s/ 2 = 162m
acceleration= final velocity - initial velocity / time
acceleration= (27m/s- 0m/s) / 3second= 9m/s2
The final velocity if the time is 6 second would be:
acceleration= final velocity - initial velocity / time
9m/s2= (final velocity - 0m/s) / 6s
final velocity= 9m/s2 * 6s= 54m/s
The distance would be:
distance= (final velocity + initial velocity) * time / 2
distance= (54m/s+ 0m/s) * 6s/ 2 = 162m
In the given case, the final velocity after 6s is 54 m/s, and the distance covered by the object in 6s = 162m
Final velocity
To find out the final velocity and distance in 6 seconds first we need to find out the acceleration of the object
Given
initial velocity, u = 0 m/s
final velocity, v = 27 m/s
Time, t = 3 sec
Solution
Using the equation of motion
[tex]v=u+at[/tex]
Putting the values:-
[tex]27= 0+a \times 3\\a=\frac{27}{3}\\= 9\ m/s^2[/tex]
So the acceleration of the object is [tex]9\ m/s^2[/tex]
Now for
t = 6 sec
Using the equation of motion
[tex]v=u+at[/tex]
And using the value of acceleration a = [tex]9\ m/s^2[/tex]
[tex]v=0+9\times6\\= 54\ m/s[/tex]
Now to calculate the distance covered in 6 sec, using the equation of motion
[tex]v^2 -u^2= 2\times a \times s[/tex]
Putting the values
[tex]54^2 -0^2 =2\times 9\times s\\2916=18\times s\\s=\frac{2916}{18} \\=162\ m[/tex]
So, the final velocity after 6s is 54 m/s, and the distance covered by the object in 6s = 162m
Learn more about final velocity:
https://brainly.com/question/13066230